(untitled) (Student’s Journal of Health Research Africa, 2022)
Background The main objective of the study was to establish the relationship between interest rates and loan repayment by examining the relationship between Central bank rate and loan repayment, loan size and loan repayment, and bargaining power and loan repayment at Finance Trust Bank. Methodology The study was carried out at Finance trust bank- Katwe main branch, Rubaga division, Kampala district using data relating to three years from 2019 to 2021 since it was a period when the commercial bank had issues regarding loan defaults. The researcher used a descriptive correlational survey design and adopted a quantitative approach to collect, analyze and interpret data for this study. The sample size of the study was 56 employees of the Finance trust bank-Katwe branch. The researcher used a simple random sampling technique to select staff that participated in this study and a purposive sampling technique was used to select managers who assisted in identifying other employees to participate in the study. Results The correlation between the Central bank rate and loan repayment was -0.120 with a Sig value of 0.117. This shows a negative weak relationship between the Central bank rate and loan repayment at Finance Trust Bank. The correlation between bargaining power and loan repayment was 0.246 with a significant value of 0.753. Therefore, there is a weak positive relationship between bargaining power and loan repayment. Conclusions Generally, bargaining power, central bank rate, and loan size have a relationship with loan repayment at Finance Trust Bank and thus influence the repayment of loans. Recommendations The commercial bank should reduce the interest rates charged on loans, give customers a chance to participate in the loan repayment schedule, and use credit scores to establish the repayment capacity of customers in order to avoid loan defaults.